PENGARUH TERAPI BEKAM TERHADAP INTENSITAS NYERI KEPALA PENDERITA HIPERTENSI DI PUSKESMAS KEMALARAJA KABUPATEN OKU - Fitri Aisyah; Sutrisari Sabrina Nainggolan; Mujahidin (LPPM STIKes Mitra Adiguna, 2024)
Increased blood pressure in patients with hypertension is mostly always accompanied by complaints of headaches. If headaches are not treated, they can really interfere with the daily activities of people suffering from hypertension. The use of salami therapy is used more than existing conventional therapy, namely the use of pharmacological drugs. Actually, there are several non-pharmacological therapies or complementary therapies that can be done to overcome this problem. One of the complementary therapies that can be done is cupping therapy. The purpose of this study was to determine whether there is an effect of cupping therapy on reducing head pain in patients with hypertension. The research design used a Quasi-Experimental Design with a Pretest-Posttest Control Group Design approach. The research population was 850 people with sampling techniques using purposive sampling with a sample size of 50 respondents consisting of two groups, namely the intervention group with wet cupping treatment and the control group. The average head pain scale in the intervention group before cupping was 3.4 and after cupping it was 1.64, while in the control group the average head pain scale was 3.22 on the Numeric Rating Scale (NRS) scale. The results of the Wilcoxon test showed a p value of 0.000. This shows that there is an effect of cupping therapy on reducing head pain in hypertensive patients. In the future, the author hopes that the cupping treatment method can be used as one of the implementations of complementary medicine at UPTD Puskemas Kemalaraja East Baturaja OKU Regency South Sumatera Province.